How Negative Frames Can Undermine Public Support for Studying Solar Geoengineering in the U.S - Bolsen, Toby; Palm, Risa; Kingsland, Justin T. (Frontiers in Environmental Science, 2022)
Scientists and policymakers have become interested in the viability of solar geoengineering as a way to manipulate the Earth’s temperature in the face of unabated global warming. This paper reports the results from a survey experiment designed to test predictions about the effects of exposure to framed messages about basic scientific research on solar geoengineering. Our findings reinforce other survey research showing that solar geoengineering is a generally unfamiliar concept, but also show that this topic has not yet become politicized. In addition, despite treatments of equal valence, we find that negative information can exert a more powerful influence than positive information on support for establishing a research program to study solar geoengineering. The results have implications for understanding how framing can influence public support for research on new technologies to mitigate climate change.